PRESS COVERAGE OF ENVIRONMENTAL NEWS IN KYRGYZSTAN AND THE ROLE OF ECO-NONGOVERNMENTAL ORGANIZATIONS - SULTANALIEVA, Chinara; FREEDMAN, Eric (CENTRAL ASIA AND THE CAUCASUS, 2015)
This article explores obstacles and conditions that environmental nongovernmental organizations face in interacting with media outlets in Kyrgyzstan. It also examines the limited scope of environmental journalism and the resulting limited ability of news outlets and eco-NGOs to help set the public agenda for discussion of policy and issues in the country. Even if such public relations interaction occurs, it is rarely effective and rarely generates influential eco/environmental articles in the media. The study is based on a content analysis of the news agency 24.kg and the newspaper Vecherniy Bishkek. It includes results of a survey and interviews with eco-NGOs representatives.